Identifikasi DNA babi sebagai metode validasi untuk autentikasi halal menggunakan polymerase chain reaction - Mariyani Mariyani; Ni nyoman Yuvita Yani; Ikhsan Hi. Amir Sene (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
To protect consumers from fake halal labelling on food products, cosmetics and medicines, a method is needed to guarantee a product's Halal. Pork is one type that is often used to mix with beef because the two types of meat have physical similarities if not carefully considered. DNA-based analysis, often used for halal authentication, is the real-time PCR method, so this study aims to prove that conventional PCR methods can detect DNA at the same concentration. This study uses two parameters: the specificity test carried out using pig DNA samples and cow and chicken DNA as a comparison. The second parameter is the detection limit test on absolute DNA carried out at 4 concentrations, namely 50, 5, 0.5 and 0.05 ng/µL, while the relative detection limit test (pork-cow mixture) with variations in pork concentration, namely 100%, 5%, 3%, 1%, and 0.5%. The analysis showed that the primers were specific to pig DNA with an absolute detection limit of 0.05 ng/µL and a relative detection limit of 0.5%. This PCR method meets the validation requirements for identifying target species so that it can be used for halal authentication of various products.